Existence of solution of Erdélyi-Kober Fractional Integral Equations Using Measure of Non-Compactness
In the present study, our main work is focused on solving the fractional order nonlinear infinite system of Erde lyi-Kober type functional integral equations in sequence space _p, p>1 by applying Hausdorff measure of non-compactness, and generalized Meir-Keeler (M-K) fixed point theorem. An example is presented to validate our existence theorem. We propose an iterative algorithm formed by homotopy perturbation along with the Adomian decomposition method to solve the considered problem with high accuracy. A numerical example is also used to show that our iterative algorithm converges strongly to the approximate solution of the proposed problem., number=3, journal=Discontinuity, Nonlinearity, and Complexity, author=Pathak, Vijai Kumar and Mishra, Lakshmi Narayan, year=2026, month=Aug., pages=701–714